The Role of Teachers in Teaching Sexual Education for Primary School Students - Supriyati, Supriyati (International Conference of Moslem Society, 2018)
Teachers in primary school have role as second parents at school by teaching and guiding students to prepare them for real life in the community. Primary school students, in the age range 6-12 years, are prepared for further development in adolescence or puberty. At that age, both male and female students are exposed to various sexual problems. Therefore, it is important to provide sexual education for primary school students. Unfortunately, schools only teach the function of reproductive organs. Teachers do not explain the dangers of sexual deviance and important values ​​of sexual education. Often teachers are very awkward when they teach something related to sex. It makes children curious and will find out more about sex by themselves. They look for it on the internet where there are a lot of inappropriate content for primary school students. The lack of sex education needs to be improved so that cases of adolescents who have premarital sex, people who are pregnant out of wedlock and other sexual deviations may be reduced in the future. Therefore, teachers are expected to play a big role in accompanying the growth and sexual development of students. This paper contains thoughts and ideas of the author in maximizing the role of teachers in teaching sexual education for primary school students.